Manfaat Etika Bisnis Buddhis Pada Minat Berwirausaha Mahasiswa Angkatan 2018 STAB Maitreyawira Pekanbaru - Edi Susanto; Rida Jelita; Irawati Irawati (Jurnal Maitreyawira, 2024)
The purpose of this study is to find out how much the Benefits of Buddhist Business Ethics on  Entrepreneurial Interests for Students of the 2018 Maitreyawira Pekanbaru Batch. The research method used in this research is a descriptive qualitative method through interviews and documentation with data collection techniques using questionnaires and observation. The results of the study concluded that there is an important role for business ethics in doing business in the life of Buddhist society, such as: a). Honesty, trust in business or business b). Mutual benefit to one another c). Have good intentions or do not mean bad to others in business activities and as a Buddhist student have very good moral integrity. This result is in line with the theory put forward by Suryana which reveals that one of the factors that influence a person's interest in entrepreneurship is personal factors (character).